Untargeted lipidomic analysis of metabolic dysfunction-associated steatohepatitis in women with morbid obesity - Laia Bertran; Jordi Capellades; Sonia Abelló; Cristóbal Richart (PLoS ONE, 2025)
Metabolic Dysfunction-Associated Steatohepatitis (MASH) represents the severe condition of Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD). Currently, there is a need to identify non-invasive biomarkers for an accurate diagnosis of MASH. Previously, omics studies identified alterations in lipid metabolites involved in MASLD. However, these studies require validation in other cohorts. In this sense, our aim was to perform lipidomics to identify the circulating lipid metabolite profile of MASH. We assessed a liquid chromatography coupled to a mass spectrometer-based untargeted lipidomic assay in serum samples of 216 women with morbid obesity that were stratified according to their hepatic diagnosis into Normal Liver (NL, n =  44), Simple Steatosis (SS, n =  66) and MASH (n =  106). First, we identified a profile of lipid metabolites that are increased in MASLD, composed of ceramides, triacylglycerols (TAG) and some phospholipids. Then, we identified that patients with SS have a characteristic profile of increased levels of ceramides, diacylglycerols DG (36:2) and DG (36:4), some TAG and a few phospholipids such as PC (32:1), PE (38:3), PE (40:6), PI (32:0) and PI (32:1). Later, in MASH patients, we found increased levels of ceramides, deoxycholic acid, a set of TAG, and some phospholipids such as PC, PE, PI and LPI; while we found decreased levels of the DG (36:0). Finally, we have reported a panel of lipid metabolites that might be used to differentiate patients with MASH from SS patients, made up of increased levels of 9-HODE some PC and PE, the LPI (16:0) and decreased levels of DG (36:0). To conclude, our investigation has suggested a lipid metabolite profile associated with MASLD and MASH. Specifically, a set of lipid metabolites seems to be discriminatory in MASH subjects compared to SS individuals. Thus, this panel of lipid metabolites could be used as a non-invasive diagnostic tool.